1983
DOI: 10.1002/er.4440070302
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study of mixed convection flow in enclosures

Abstract: A numerical study of the velocity and temperature distributions that arise in a water body due to a thermal discharge such as that in a heat rejection or a sensible energy storage system, has been carried out. The time‐dependent distributions, as well as the steady‐state solutions, have been obtained by the use of the alternating direction implicit method for the coupled vorticity transport and energy equations. The numerical procedure employed is outlined, indicating some of the salient features and problems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Several investigators have studied the recirculating flow in enclosures caused by the discharge of hot, buoyant fluid particularly for laminar flow. Wada (1967, 19681, Park andSchmidt (1973), Oberkampf and Crow (1976), Cabelli (1977), Sliwinski (1980), Jaluria (1980, 1981), and Jaluria and Gupta (1980) studied the recirculating flow in water bodico for various fluw configurations. Figures 2-8 through 2-10 indicate some of the results.…”
Section: -2mentioning
confidence: 99%
“…Several investigators have studied the recirculating flow in enclosures caused by the discharge of hot, buoyant fluid particularly for laminar flow. Wada (1967, 19681, Park andSchmidt (1973), Oberkampf and Crow (1976), Cabelli (1977), Sliwinski (1980), Jaluria (1980, 1981), and Jaluria and Gupta (1980) studied the recirculating flow in water bodico for various fluw configurations. Figures 2-8 through 2-10 indicate some of the results.…”
Section: -2mentioning
confidence: 99%
“…It is observed that for considered range of Ri , heat transfer rate and temperature field are strongly influenced by Pr , whereas very little variation is observed in the flow characteristics. Jaluria and Gupta numerically studied steady as well as transient velocity and temperature fields using the alternating direction implicit method along with Gauss Seidel method. Liao and Lin carried out a study of natural and mixed convection of rotating and stationary centered cylinder in a 2D square cavity, with various rotational speeds.…”
Section: Introductionmentioning
confidence: 99%
“…Convective heat transfer of conventional heat-transfer fluids (such as air, water or oil) in cavities (such as square, wavy, inclined, cylindrical annuli, or triangular) has long been a question of great interest in a wide range of fields [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Flow and heat transfer from such irregular surfaces are often encountered in many engineering applications such that it is in great need to enhance heat transfer in the cooling system of microelectronic devices, flat-plate solar collectors, flat plate condensers in the refrigerator and underground cable system, etc.…”
Section: Introductionmentioning
confidence: 99%